Exploring Thematic Progression in Selected Bachelor of Arts Dissertation Abstracts: A Systemic Functional Linguistics Approach - LOKO, Djima Crépin (My University, 2023)
Writing a dissertation abstract seems sometimes to be too demanding for novices in the field of scientific research in many ways, especially at the level of thematic progression. The present study aims at describing, analysing, and interpreting the different linguistic features that predict Themes patterns and thematic progression in ten (10) abstracts culled from Bachelor of Arts (B.A.) dissertations through a mixed method of research. The analyses have taken into account such salient Theme patterns as re-iteration, zig-zag, and multiple Theme patterns through the description of the structural configuration of the clauses within the selected abstracts from a systemic-functional perspective. The discussion has revealed the mechanisms that create cohesive texts in each of those B.A. dissertation abstracts. The findings disclose the way the thematic properties have allowed each candidate to write his/her abstract as a short paragraph that summarises the gist of a whole dissertation following the academic requirements.
Keywords: Theme-Rheme theory; Systemic Functional Linguistics (SFL); textual meaning; B.A dissertation.